Recent advances in methylation modifications of microRNA - Ning Su; Xiaohang Yu; Ming Duan; Ning Shi (Genes and Diseases)
microRNAs (miRNAs) are short single-stranded non-coding RNAs between 21 and 25 nt in length in eukaryotic organisms, which control post-transcriptional gene expression. Through complementary base pairing, miRNAs generally bind to their target messenger RNAs and repress protein production by destabilizing the messenger RNA and translational silencing. They regulate almost all life activities, such as cell proliferation, differentiation, apoptosis, tumorigenesis, and host–pathogen interactions. Methylation modification is the most common RNA modification in eukaryotes. miRNA methylation exists in different types, mainly N6-methyladenosine, 5-methylcytosine, and 7-methylguanine, which can change the expression level and biological mode of action of miRNAs and improve the activity of regulating gene expression in a very fine-tuned way with flexibility. In this review, we will summarize the recent findings concerning methylation modifications of miRNA, focusing on their biogenesis and the potential role of miRNA fate and functions.